2014
DOI: 10.1128/iai.01976-14
|View full text |Cite
|
Sign up to set email alerts
|

The Periodontal Pathogen Porphyromonas gingivalis Induces Expression of Transposases and Cell Death of Streptococcus mitis in a Biofilm Model

Abstract: Oral microbial communities are extremely complex biofilms with high numbers of bacterial species interacting with each other (and the host) to maintain homeostasis of the system. Disturbance in the oral microbiome homeostasis can lead to either caries or periodontitis, two of the most common human diseases. Periodontitis is a polymicrobial disease caused by the coordinated action of a complex microbial community, which results in inflammation of tissues that support the teeth. It is the most common cause of to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 43 publications
0
44
0
Order By: Relevance
“…Filifactor alocis , Peptostreptococcus stomatis and species from the genera Prevotella , Megasphaera , Selenomonas , and Desulfobulbus ) that have now been shown by metagenomic analyses to exhibit as good (or better) a correlation with disease as traditional pathogenic species, such as P. gingivalis , Tannerella forsythia , and Treponema denticola [1417]. Consistent with this notion, a recent metatranscriptomic study revealed that the majority of virulence factors upregulated in the microbiome of periodontitis patients is primarily derived from previously underappreciated species that were not traditionally implicated in periodontitis [18]. It is possible that pathobionts might outcompete keystone or keystone-like pathogens such as P. gingivalis and T. forsythia in late stages of periodontal disease pathogenesis.…”
Section: Interbacterial Interactionsmentioning
confidence: 89%
See 1 more Smart Citation
“…Filifactor alocis , Peptostreptococcus stomatis and species from the genera Prevotella , Megasphaera , Selenomonas , and Desulfobulbus ) that have now been shown by metagenomic analyses to exhibit as good (or better) a correlation with disease as traditional pathogenic species, such as P. gingivalis , Tannerella forsythia , and Treponema denticola [1417]. Consistent with this notion, a recent metatranscriptomic study revealed that the majority of virulence factors upregulated in the microbiome of periodontitis patients is primarily derived from previously underappreciated species that were not traditionally implicated in periodontitis [18]. It is possible that pathobionts might outcompete keystone or keystone-like pathogens such as P. gingivalis and T. forsythia in late stages of periodontal disease pathogenesis.…”
Section: Interbacterial Interactionsmentioning
confidence: 89%
“…Consequently, the distribution of P. gingivalis and S. cristatus in human subgingival plaque is negatively correlated, and S. cristatus attenuates P. gingivalis -induced bone loss in mice [35]. Such antagonistic interaction may lead to a ‘Red Queen’ effect, as P. gingivalis can induce cell death of another oral streptococcus, S. mitis [18]. Overall, however, the periodontal microbiota conforms more with the ‘Black Queen Hypothesis’ [36], whereby functions that are energetically costly and are discarded by ‘cheaters’, are nevertheless retained by a subset of community members as they benefit the entire community.…”
Section: Interbacterial Interactionsmentioning
confidence: 99%
“…During progression of periodontitis, there is a reduction in the fraction of streptococci present in the biofilm. Studies have shown that P. gingivalis induces S. mitis cell death (10-fold increase); and DNA fragmentation, and increases production of reactive oxygen species by up to 25-fold in an in vitro biofilm system by an unknown mechanism, thus shaping the oral microbiome to its advantage [28]. Therefore, it could be reasoned that successive biofilm formation may play a role in major periodontal species pathogenicity.…”
Section: Early and Late Colonizersmentioning
confidence: 99%
“…These are also clustered as the “red complex” species [28]. Studies investigating colonization of human gingival multi-layered epithelium by 10-species subgingival biofilm ( F. nucleatum, Campylobacter rectus, V. dispar, P. gingivalis, P. intermedia, T. forsythia, T. denticola, A. oris, S. anginosus and S. oralis ) or its 7-species variant lacking P. gingivalis, T. forsythia and T. denticola , evaluated the relative effects of the "red complex" species on the composition and cell-colonizing capacities of the remaining seven species [61].…”
Section: Subgingival Biofilmsmentioning
confidence: 99%
“…Material adhering to the chamber material during S. mitis infection at 3 days, however, appears to be comprised primarily of neutrophils, and individual bacteria were present but not common. This strain has been shown to form biofilm under appropriate conditions in vitro (49), suggesting that biofilm forms in the chamber model as well. Biofilm formation may contribute to the persistence of the bacteria in the EP-infected chambers and may account to some extent for the difference in clearance between EP and S. mitis.…”
Section: Discussionmentioning
confidence: 99%